Comparative Study of Free Amino Acid Profiles in Underground Organs of Several Species of the Genus Rumex During Different Phases of the Vegetation Cycle - A. M. Poluyanov; U. A. Matvienko; A. Yu. Sokolova; A. E. Savelyeva; N. A. Durnova; N. V. Bobkova (Разработка и регистрация лекарственных средств)
Introduction. Amino acids (AA), the primary metabolites in plants, play a crucial role in various physiological processes, including the synthesis of phenolic compounds. Drug products and dietary supplements made from medicinal plants can become a rich source of both nonessential and essential amino acids. High levels of free amino acids found in herbal raw material often indicate the presence of biotic and abiotic stress in the plants. Therefore, understanding the dynamics of bioactive compound accumulation in plants throughout their phenological phases of development is critical to optimizing their potential health benefits.Aim. To compare qualitative composition and dynamics of AA accumulation in the underground organs of four representatives of the Rumex genus: R. confertus, R. crispus L., R. obtusifolius L., R. aquaticus L. of three different vegetative phases.Materials and methods. Water extracts from underground organs of the studied plants were analyzed using two different methods for qualitative and quantitative analysis. Extracts were applied to the chromatographic plates TLS Silica gel 60 F254 (Merk, Germany) 20 × 20 cm with a micro-syringe (LLC "Tsvet", Russia). After elution, the plates were treated with a 2 % ninhydrin solution. Quantitative analysis was carried out using the SF-2000 spectrophotometer (LLC "OKB Spectr", Russia).Results and discussion. The amino acid profile of the underground organs of R. confertus, R. crispus L., R. obtusifolius L., R. aquaticus L. during three vegetative phases was determined using the TLC method; the quantitative analysis performed using spectrophotometry.Conclusion. The most diverse amino acid (AA) profiles were found in the withering phase in all Rumex species, with up to 9 amino adsorption zones. In contrast, the least diverse AA profiles were observed in the flowering phase, ranging from 2 to 4 adsorption zones. The quantitative content of AA was lowest in the flowering phase, increased during the regrowth phase, and peaked in the withering phase. However, R. crispus L. showed an unusual pattern, with the highest quantitative content of AA detected in the regrowth phase.